Electroacupuncture may alleviate behavioral defects via modulation of gut microbiota in a mouse model of Parkinson's disease. Issue 5 (October 2021) - Han, Qiu-Qin; Fu, Yi; Le, Jia-Mei; Pilot, Adam; Cheng, Si; Chen, Pei-Qing; Wu, Hailong; Wan, Guo-Qing; Gu, Xue-Feng
Objective: Parkinson's disease (PD) is a chronic neurodegenerative disease involving non-motor symptoms, of which gastrointestinal disorders are the most common. In light of recent results, intestinal dysfunction may be involved in the pathogenesis of PD. Electroacupuncture (EA) has shown potential effects, although the underlying mechanism remains mostly unknown. We speculated that EA could relieve the behavioral defects of PD, and that this effect would be associated with modulation of the gut microbiota. Methods: Mice were randomly divided into three groups: control, PD + MA (manual acupuncture), and PD + EA. MPTP (1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine) was used to establish the mouse model of PD. Rotarod performance tests, open field tests, and pole tests were carried out to assess motor deficiencies. Immunohistochemistry was conducted to examine the survival of dopaminergic neurons. 16S ribosomal RNA (rRNA) gene sequencing was applied to investigate the alterations of the gut microbiome. Quantitative real-time polymerase chain reaction (PCR) was performed to characterize the messenger RNA (mRNA) levels of pro-inflammatory and anti-inflammatory cytokines. Results: We found that EA was able to alleviate the behavioral defects in the rotarod performance test and pole test, and partially rescue the significant loss of dopaminergic neurons in the substantia nigra (SN) chemically induced by MPTP in mice. Moreover, the PD + MA mice showed a tendency toward decreased intestinal microbial alpha diversity, while EA significantly reversed it. The abundance of Erysipelotrichaceae was significantly increased in PD + MA mice, and the alteration was also reversed by EA. In addition, the pro-inflammatory cytokines interleukin (IL)-6 and tumor necrosis factor (TNF)-α were substantially increased in the SN of PD + MA mice, an effect that was reversed by EA. Conclusion: These results suggest that EA may alleviate behavioral defects via modulation of gut microbiota and suppression of inflammation in the SN of mice with PD, which provides new insights into the pathogenesis of PD and its treatment.